Accounting Change and Institutional Capacity: The Case of a Provincial Government in Indonesia - Harun Harun; Haryono P. Kamase (Australasian Accounting, Business and Finance Journal, 2012)
This study examines a reporting system change of a provincial government in Indonesia. The study also draws attention to the institutional capacity of the provincial administration and implementation problems it encountered in adopting an accrual accounting system. Following the work of Lapsley and Pallot (2000), this study uses economic and institutional perspectives in conceptualising how an accounting change has been undertaken. The study shows that from an economic based perspective, the adoption of the new reporting system was stimulated by the wish to improve government organisations’ performance in the country. It is also found that the change of the reporting system was not accompanied by the separation of the roles of elected local officials (i.e. the governor) and local parliamentary members as politicians and decision-makers in the allocation of funding and budget formulation in the provincial government. This situation undermines the instrumental roles of accounting for decision making. Moreover, drawing upon institutional theory, the adoption of the new reporting system at provincial level in the country is indicated by the presence of coercive pressure as local administrations in Indonesia are required to comply with rules imposed by the central government. However, based on the experience of a provincial government in implementing the new accounting system, the policy to adopt the new accounting regime fails to recognise a low level of institutional capacity of local administrations. As a consequence, the institutionalisation of the new accounting system has yet to bring intended outcomes. In this vein, the role of accounting as a political tool for controlling people overshadows its roles for efficiency and performance improvement. As the study demonstrates the use of mixed methodological perspectives (i.e. economic and institutional theories) is useful to fully capture and understand the dynamic process of accounting change in a specific setting.
Keywords: Accrual accounting; accountability; performance improvement; Indonesian local government